Grain Shape Dynamics for Molecular Simulations at the Mesoscale. Issue 9 (16th August 2020) - Martzel, Nicolas; Dequidt, Alain; Devémy, Julien; Blaak, Ronald; Garruchet, Sebastien; Latour, Benoit; Goujon, Florent; Munch, Etienne; Malfreyt, Patrice
Abstract: Coarse‐graining routines are necessary for simulating systems involving large molecules. However, their accuracy is limited by excessive simplifications that are made during the upscaling procedure. The time autocorrelation of the shape anisotropy of grains in cis ‐polybutadiene chains is computed, and it is concluded that the image of a grain as an undeformable object is no longer valid at high level of coarse‐graining. A model for the joint dynamics of the centers of mass and the shapes of grains, which are calculated from the positions of the atoms they represent, is introduced. The model reproduces the distribution and dynamics of the shape of a single‐grain oligomer in various solvents, opening a route to physical modeling of complex systems such as proteins, biological cells, or realistic polymer melts. Abstract : The shape of polymer segments is not spherical and changes in time. Although their internal structure is usually averaged out in a static spherical model, this approximation is not always satisfactory. A more accurate description is given by deforming and rotating ellipsoids. Herein, it is shown how to simulate this dynamics of shape and orientation efficiently and apply it to solvated oligomers.